IMPLEMENTASI ME-FINANCE DENGAN METODE AGILE BERBASIS WEB - Della Novita; Alfannisa Annurrullah Fajrin (LPPM Universitas Putera Batam, 2025)
The financial management practices in mosques still depend on traditional methods, which makes them susceptible to inaccuracies and inefficiencies. This research seeks to create a web-based financial application utilizing the Agile methodology to improve efficiency, accuracy, and financial reporting. The application is targeted at mosque treasurers, incorporating essential features like transaction logging, financial reporting, and graphical analysis. The research approach consists of data gathering, system design, development, testing, and deployment. To ensure both functionality and user satisfaction, Black Box Testing and User Acceptance Testing (UAT) were performed. The findings indicate that the application successfully automates financial management, minimizing errors and enhancing accessibility